Impact of Reduction of Waste and Waste, Green Employee Behavior and Reduction of Resource Use on Environmental Strategy: Manufacturing Companies top management’s Perception (Journal of Social Sciences Review, 2023)
This study explores the impact of reduction of waste and waste, green employee Behavior and reduction of resource use on environmental strategy in manufacturing companies of Sindh, Pakistan. Using a cross-sectional design and a sample of 220 firms, data was collected through face-to-face surveys conducted from August 1 to October 31, 2022. The questionnaire adopted in this study focused on including the reduction of waste and waste, green employee behavior and reduction of resource use. The collected data were analyzed using structural equation modelling (SEM) to test the proposed hypotheses. The findings suggest that these variables have a positive and significant impact on environmental strategy, indicating that these variables can be valuable tools for promoting environmental strategy in the manufacturing sector of Sindh, Pakistan. These results have practical implications for manufacturing companies in Sindh, Pakistan, as it suggests that top management should prioritize the development of effective strategies to promote the reduction of waste and waste, green employee behavior and reduction of resource use in the future strategies.
Keywords: Environmental Strategy; Green Employee Behavior; Reduction of Waste and Emissions; Reduction of Resource Use